Asset Complementarity, Resource Shocks, and the Political Economy of Property Rights. (August 2018) - Silve, Arthur
Collaboration between two groups that may invest their resources in a common productive activity has the potential to lead to conflict over the output of that activity. This article examines the stakes of such conflict as well as the willingness for parties to subject themselves to a third-party arbiter. The model highlights three determinants of conflict and of investment in credibility-enhancing institutions: the value of the output, the relative endowments of the parties, and the mutual benefits of collaboration. In particular, the analysis shows that complementarity between the groups' resources lowers the stakes of political conflict and increases the incentives to commit. The model thus suggests a new mechanism through which we can understand the frequency of conflict and the poor institutions associated in countries with mineral resources. The model's predictions also help us to understand how Mauritius avoided the resource curse and was able to develop sustainable economic growth.